Communicative effort. Toward a true to everyday life intercultural (foreign language) teacher training - Błażek, Agnieszka (Glottodidactica, 2018)
Intercultural (foreign language) teacher training tends to concentrate on selective case studies developed to show communicative problems, caused by their very special intercultural and multilingual characteristics. It also tends to make a big promise of a rapid improvement in intercultural communication in a multicultural and multilingual society by transferring the solutions for intercultural communicative problems to the students’ own experience. Such an approach fails to take into account the fact that encounters with inadequate communicative acts (behaviours/speech acts) determined by cultural and/or language differences are a daily experience of everybody and require a lot of communicative effort in order to prevent intercultural problems before they happen. The following article discusses what is meant by communicative effort, how past studies on the intercultural competence of (foreign language) teachers account on communicative effort, and how to prepare students to undertake communicative effort in their daily communicative activities in a multicultural and multilingual society.